Sick Role and a Critical Evaluation of its Application to our Understanding of the Relationship between Physician and Patients - Heidarnia, Mohmmad Ali; Heidarnia, Ali (Novelty in Biomedicine, 2016)
This article examines the sick role theory introduced by Talcott Parsons applying his background theoretical context. It additionally attempts to ascertain how the sick role theory delineates the physician-patient relationship. The theory seems to have roots in certain salient conceptions in the Parsonian sociology, including his evolutionary interpretation of modern society that plays a major part in outlining the ‘Pattern Variables’. To provide a plausible perception of what Parsons ponders about, the definitions of health, illness and the sick person are examined in the next stage. Critical perspectives offered here have been engendered through the process of comprehension of the theory and are related to certain aspects of that. It is finally concluded how a more precise understanding of the Parsons’ work can lead to a more productive patient-doctor relationship.